GAMMA-GLUTAMYLTRANSFERASE DAN APOLIPOPROTEIN B DENGAN SINDROMA METABOLIK - Tahono .; M.I. Diah Pramudianti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
The number of Metabolic Syndrome (MS) patient has been rapidly increased. Diabetes Mellitus (DM) is a risk factor of coronaryheart disease that increased four fold in the general population. Gamma-glutamyltransferase (GGT) is located on the external surfaceof most cells and mediates the uptake of glutathione, which is an important component of intracellular antioxidants defenses. The aimsof this study was to analyze the correlation between GGT, Apolipoprotein B and metabolic syndrome parameters, a high sensitivityC-Reactive Protein (hs-CRP) as a marker of inflammation, and glutathione peroxidase (GPx) as an antioxidant marker in type 2 DMpatients. This study used a cross sectional design. The subject of this study was type 2 DM patients who came to the EndocrinologySubdivision of Internal Medicine Department and Laboratory of Clinical Pathology at Dr. Moewardi Hospital Surakarta. To analyze thisresult, the researchers used Spearman (r) correlation test with significance degree p < 0.05 and confidence interval 95%.The gammaglutamyltransferase serum showed a weak positive correlation with waist circumference (r = 0.18; p = 0.045) and Apo B with fastingblood glucose (r = 0.32; p = 0.001); a mild positive correlation between Apo B and triglyceride (r = 0.45; p = 0.001); a weak negativecorrelation between HDL cholesterol and GGT (r = –0.22; p = 0.020) and Apo B (r = –0.20; p = 0.027); a weak positive correlationbetween hs-CRP and GGT (r = 0.38; p = 0.001), and Apo B (r = 0.18; p = 0.042); and a weak negative correlation between Apo Band GPx (r = –0.22; p = 0.019). Gamma-glutamyltransferase examination is superior to notice any inflammatory process than apoB(r = 0.38 vs. R = 0.18), whereas apoB is superior as a predictor of inflammation than GGT (r = –0.51 vs. R = –0,20). Gammaglutamyltransferase serum as an early marker of oxidative stress and Apo B was related to inflammation at the metabolic syndromeand diabetes. Measurement of GGT serum is reliable, easy, and not expensive, it might have important implications both clinically andepidemiologically